Synthesis and Characterization of 6- (4- Acetylphenyl azo) - 3 -Aminobenzoic Acid Complexes for Some Transition Metals - Abaas Obaid Hussein (Journal of Global Pharma Technology, 2016)
Azo dye 6-(4-acetylphenyl azo)-3-aminobenzoic acid was produced by grouping the diazonium salt from 4-aminoacetophenone for 3-aminobenzoic acid. Geometry of azo - ligand was resolved on origin of elemental analysis, spectroscopic studies such as 1H and 13CNMR, FTIR and UV-Vis. Handling produced azo ligand for transition metal chelates at aquatic ethanol for a 1:2 metal: ligand ratio, as well in perfect pH. The metal chelates have been described by utilizing atomic, absorption flame, elemental analysis, FTIR, and UV-Vis, as well conductivity and magnetic susceptibility mechanism. Nature for produced compounds, have been studied, obeyed mole ratio as well, methods of continuous, variation, Beer's law yielded up a condensation rate (1×10-4 - 3×10-4M).  High molar were absorbtivity, were observed for complex solutions. On origin data a tetrahedral geometry were assigned for the produced complexes. Biological activity of the produced compounds was assayed. Keywords: Metal chelate, Azo dyes, Complexes, Biological activity.